THE KNOWLEDGE REGARDING THE NUTRITIONAL CONTENT OF SEA URCHIN GONADS (DIADEMA SETOSUM) AMONG HOUSEWIVES LIVING IN COASTAL AREAS - Muchtar, Febriana; Maharani, Maharani; Landepasa, Erin; Marjani, Marjani; Giu, Wa Ode Sitti Hajra; Afriandi, Afriandi (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Coastal areas are endowed with diverse marine biodiversity, providing numerous sources of animal-based food, including sea urchins. Sea urchins have edible part called the gonad or roe which contain high nutrition and bioactive components. Sea urchin gonads are frequently collected and sold either to intermediaries or directly to consumers. This study evaluated the knowledge of housewives who lived in coastal areas regarding the nutritional value of sea urchin gonads. This quantitative descriptive study was fconducted in Leppe Village, Soropia District, Konawe Regency, in August 2024. There were 37 housewives with young children who were engaged in the collection of sea urchin gonads who participated in this study. Data were collected using a structured questionnaire that assessed knowledge of the nutritional content and health benefits of sea urchin gonads. The results indicated that 13 respondents (35.14%) possessed good knowledge, while 24 respondents (64.86%) demonstrated limited knowledge. The study concludes that the overall knowledge of coastal housewives regarding the nutritional content of sea urchin gonads is relatively low.